PERAN PRODUSER DALAM PEMBUATAN MUSIC VIDEO “EVERYTHING GOES ON” (KOBO KANAERU REMAKE VERSION) - Josephine Stella; Arrya Dianta (Jurnal Humaniora & Sosial Sains, 2025)
The cultural landscape entering Indonesia is increasingly diverse, including music, cosplay, and virtual YouTube. This is evident in the abundance of animated and cosplay content on digital platforms. This topic is also supported by the development of new media. Content with a duration of less than 5 minutes is more frequently watched by the audience. A producer has the right to determine the story, supervise, and provide direction to the team. Therefore, the researcher, as producer, created a music video covering the song "Everything Goes On" by Porter Robinson, which was also covered by Kobo Kanaeru, a virtual YouTuber from the Indonesian agency Hololive ID. Kobo made a cover of the song "Everything Goes On" in the form of a lyric video. The work created by the researcher entitled Music Video “Everything Goes On” (Kobo Kanaeru Remake Version)” is packaged as a cinematic music video. The presentation that will be shown is a live action featuring the talent of cosplayer Kobo and other supporting characters who will make the fictional virtual character seem real. That is what differentiates it from previous works. The main purpose of making this music video is for entertainment, motivation, and to create a work that is not boring. This kind of research as a producer to understand how to create a music video that can stimulate the thoughts, emotions, and interaction of the audience with the work. As a producer, the researcher is fully responsible for all stages of production, from pre-production to post-production.